Why can't we be friends? Exploring factors associated with cat owners' perceptions of the cat-cat relationship in two-cat households - Khoddami, Sherry; Kiser, Makayla C.; Moody, Carly M. (Frontiers in Veterinary Science, 2023)
Most research examining cat behavior in multi-cat households lacks focus on one group size. This gap in knowledge reduces generalizability of research findings to specific compositions of cats in multi-cat households. Given that many cat-owning households in Canada and the US are comprised of two cats, the following study used a cross-sectional survey to explore cat owners’ perceptions of the cat-cat relationship in two-cat households in Canada and the US. A total of 6,529 owners of two cats completed the online questionnaire. Descriptive statistics were used to summarize the data and a logistic regression model used to assess various explanatory variables (i.e., household, management, and cat-specific factors) associated with participants perceiving their cats’ relationship as negative. The logistic regression model showed that owners of two-cat households are more likely to perceive their cats’ relationship as negative if both cats are spayed females, adult or mature, have a large gap in age, not related, one or both have access to the outdoors, or show aggression towards people or other animals in the home. Having multiple litterbox and feeding areas were also associated with a more negative cat-cat relationship. Overall, the complex interplay, directionality, and temporality of these factors requires further investigation for a full understanding of how to improve the cat-cat relationship in two-cat households. More research is needed to provide evidence-based recommendations for managing and supporting a positive cat-cat relationship in the home.